2020
DOI: 10.1177/1556984520908962
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serratus Anterior Plane Block for Pain Relief in Patients Undergoing MIDCAB Surgery

Abstract: Objective The minimally invasive direct coronary artery bypass (MIDCAB) surgery is associated with severe chest pain in the first 2 to 3 postoperative days; this may delay the patient recovery. In this randomized controlled trial we evaluated the role of serratus anterior plane (SAP) block for postoperative pain relief in patients undergoing MIDCAB surgery. Methods Patients undergoing MIDCAB surgery were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…10 The results of SAPB may at times be conflicting. [11][12] In a randomized trial (N = 50: single institution) evaluating SAPB for analgesia after minimally invasive direct coronary artery bypass, Gautam et al reported significantly reduced postoperative pain scores and opioid requirements in the setting of SAPB. 11 In this trial, the control group received no regional analgesic block and systemic analgesia with titrated opioid, including fentanyl.…”
Section: Editorialmentioning
confidence: 99%
See 4 more Smart Citations
“…10 The results of SAPB may at times be conflicting. [11][12] In a randomized trial (N = 50: single institution) evaluating SAPB for analgesia after minimally invasive direct coronary artery bypass, Gautam et al reported significantly reduced postoperative pain scores and opioid requirements in the setting of SAPB. 11 In this trial, the control group received no regional analgesic block and systemic analgesia with titrated opioid, including fentanyl.…”
Section: Editorialmentioning
confidence: 99%
“…[11][12] In a randomized trial (N = 50: single institution) evaluating SAPB for analgesia after minimally invasive direct coronary artery bypass, Gautam et al reported significantly reduced postoperative pain scores and opioid requirements in the setting of SAPB. 11 In this trial, the control group received no regional analgesic block and systemic analgesia with titrated opioid, including fentanyl. 11 In a retrospective observational trial (N = 197), Moll et al evaluated analgesic options (SAPB v paravertebral block v titrated systemic opioid) after minimally invasive direct coronary artery bypass at a single institution.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations